Project delivery systems : The partnering concept in integrated and non-integrated construction projects - Sari, Endah Murtiana; Irawan, Agustinus Purna; Wibowo, Mochamad Agung; Siregar, Januar Parlaungan; Praja, Arief Kusuma Among (MDPI, 2023)
The project delivery system has a large effect in determining the quality of a project. Strategic plans determined by the owner in the project initiation phase must ensure that project performance indicators in the form of cost and quality as well as time are accomplished. A concept of partnering that is well-managed and planned from the initiation phase will determine the quality of the construction project. Increasing the maturity of partnering is needed in order to achieve better project performance indicators. The concept of partnering in integrated and non-integrated projects has a different pattern. This study intends to discuss the concept of partnering and then recommend several key strategies according to the project life cycle. Research this study is quantitative, analyzing secondary data in the form of weekly meetings and project reports with the comparative method and cause-and-effect analysis. The results show that in the phase above 51% of ongoing projects, there is a significant difference in the pattern of partnering between integrated and non-integrated projects. In order to improve deeper partnering, this research reveals several prerequisites that must be met in order to carry out effective partnering in non-integrated projects. This research may benefit owners, contractors, and stakeholders who want to develop their understanding and knowledge of the concepts of partnering and the maturity of partnering, which will be new strategies for developing and improving project delivery systems. This study focuses on a topic from the Sustainable Development Goals (SDGs), specifically partnership for the goal.